Cesarean scar niche: An evolving concern in clinical practice. Issue 2 (21st November 2022) - Armstrong, Fionnvola; Mulligan, Karen; Dermott, Roisin Mac; Bartels, Helena C.; Carroll, Stephen; Robson, Michael; Corcoran, Siobhan; Parland, Peter Mc; Brien, Donal O.; Brophy, David; Brennan, Donal J.
Abstract: Increasing cesarean section rates have led to an increased awareness of associated complications such as the formation of cesarean scar niche, defined as an indentation at the site of the cesarean scar with a depth of at least 2 mm, diagnosed by ultrasound or magnetic resonance imaging. The precise prevalence of cesarean scar niche is unclear. The cause of a cesarean scar niche appears to be multifactorial and likely a combination of technical factors (low incision location), anatomical factors (uterine retroflexion), and patient factors, which might impair healing (body mass index, smoking, maternal age). Most patients with cesarean scar niche are asymptomatic; however, women can present with postmenstrual bleeding, pelvic pain, and subfertility. In pregnancy, cesarean scar niches have been associated with placenta accreta spectrum disorder and uterine rupture. Treatment should be reserved for symptomatic women. Hormonal treatment using either the combined oral contraceptive pill or a progesterone‐containing intrauterine device may address irregular vaginal bleeding. Surgical management should be reserved for those in whom hormonal manipulation has failed or is contraindicated. The aim of this review was to summarize current literature pertaining to the cause, prevalence, diagnosis, and symptoms of cesarean scar niche and to make recommendations for managing this relatively new condition. Synopsis: This review aims to summarize the current literature pertaining to the aetiology, prevalence, diagnosis, and symptoms of cesarean scar niche, as well as provide recommendations for managing this relatively new condition.